2016
DOI: 10.15690/vramn623
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences of Spectral Characteristics of Baseline EEG in Primary School-Aged Children

Abstract: Формирование структурно-функциональной органи-зации мозга в постнатальном онтогенезе продолжается в течение длительного периода [1,2]. Младший школь-ный возраст характеризуется интенсивным созреванием центральной нервной системы (ЦНС), существенными преобразованиями в коре больших полушарий, и как следствие, этого значительными изменениями характера электроэнцефалограммы (ЭЭГ) [3,4]. В исследованиях разных авторов описаны возрастные изменения ЭЭГ у детей и подростков [5−7]. Доказано, что с возрастом происходит… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The EEG reaction to hyperventilation undergoes permanent changes during brain maturation and development. Different studies widely describe it ( 22 , 39 , 40 ). We should point out that children, adults, and the elderly have different sensitivity to the hypocapnia developed during hyperventilation ( 36 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EEG reaction to hyperventilation undergoes permanent changes during brain maturation and development. Different studies widely describe it ( 22 , 39 , 40 ). We should point out that children, adults, and the elderly have different sensitivity to the hypocapnia developed during hyperventilation ( 36 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The investigations related to functional features of brain maturation using EEG shown differences between girls and boys. Gender-related EEG differences in 7–10-year-old children indicate the prevalence of brain maturity in girls compare to boys ( 40 , 44 ). The study confirmed the increase in alpha rhythm dominant frequency and modulation in 7-year-old girls.…”
Section: Discussionmentioning
confidence: 99%